Trauma resuscitation: can team behaviours in the prearrival period predict resuscitation performance?. (20th February 2017) - Su, Lillian; Kaplan, Seth; Burd, Randall; Winslow, Carolyn; Hargrove, Amber; Waller, Mary
Abstract : Background: Optimising team performance is critical in paediatric trauma resuscitation. Previous studies in aviation and surgery link performance to behaviours in the prearrival period. Objective: To determine if patterns of human behaviour in the prearrival period of a simulated trauma resuscitation is predictive of resuscitation performance. Design: Twelve volunteer trauma teams performed in four simulation scenarios in a paediatric hospital. The scenarios were video recorded, transcribed and analysed in 10-second intervals. Variation in the amount of utterances per team member in the prearrival period was compared with team performance and implicit coordination during the resuscitation. Key results: Coders analysed 18 962 s of video. They coded 5204 team member utterances into one of eight communication behaviour categories. Inter-rater reliability was excellent (an average of 83.1% across all four scenarios). The average number of communications occurring during the prearrival period was 18.84 utterances, with a range of 2–42 and a SD of 9.55. The average length of this period was almost 2 minutes (mean =117.30 s, SD=39.20). Lower variance in team member communication during the prearrival better was associated with better implicit coordination (p=0.011) but not team performance (p=0.054) during the resuscitation. Conclusion: Patterns of communication in the prearrival trauma resuscitation period predicted implicit coordination and a trend towards significance for team performance which suggests further studies in such patterns are warranted.